Control of Hydroid Colony Form by Surface Heterogeneity. - Leo W Buss; Evan D Buss; Christopher P Anderson; Michael Power; Joseph Zinter (PLoS ONE, 2016)
The colonial hydroid Podocoryna carnea grows adherent to surfaces progressing along them by a motile stolon tip. We here ask whether the stolon tip grows preferentially within grooves etched in silicon wafers. In a series of pilot experiments, we varied the dimensions of grooves and found that stolons did not utilize grooves with a width:depth of 5:5 μm or 10:10 μm, occasionally followed grooves 25:25 μm in size, and preferentially grew within grooves of a width:depth of 50:50 μm and 100:50 μm. We then grew colonies in grids, with fixed 50:50 μm width:depth channels intersecting at 90° every 950, 700, 450, or 150 μm. We find that stolons grew within grooves early in colony ontogeny, but remained restricted to them only in the grid pattern with channel intersections every 150 μm. Finally, we created a grid in the shape of the Yale Y logo, with channels of 50:50 μm width:depth and intersections every 100 μm. The resulting colonies conformed to that of the logo. Our findings demonstrate that stolons respond to surface heterogeneity and that surface etching can be used to fabricate microfluidic circuits comprised of hydroid perisarc.